Training delivery faux pas : daily diary of a trainer - Sinha, Anamika; Varkkey, Biju ([London] : SAGE, 2016)
The case examines training conducted by a young professional in the capacity of an external trainer. The client organization, a mobile handset manufacturer, had multiple channels of sales. As a result, sales executives faced channel conflicts from their own partners. There were mixed strategy signals, whereas the training was designed to focus on skill development. The trainer, without having carried out the TNA, agreed to deliver her training merely based on some discussions and mandates passed on to her. The outcome was a mismatch between training content and participant demand.
Originally Published in: Sinha, A., & Varkkey, B. (2015). Training Delivery Faux Pas: Daily Diary of a Trainer. P&IR0230. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Employees -- Training of -- Case studies; Human capital -- Management -- Case studies